2014
DOI: 10.1007/s00167-014-3108-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative ligament laxity influences functional outcome 1 year after total knee arthroplasty

Abstract: Purpose To find out if there is an association between ligament laxity measured intraoperatively and functional outcome 1 year after total knee arthroplasty (TKA).MethodsMedial and lateral ligament laxities were measured intraoperatively in extension and in 90° of flexion in 108 patients [122 knees; median age 70 (range 42–83) years]. Mechanical axes were measured preoperatively and at 1-year follow-up. Outcome measures were the Knee Injury and Osteoarthritis Outcome Score (KOOS), the Knee Society Clinical Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 40 publications
3
66
0
2
Order By: Relevance
“…It's a major risk factor in the development of OA 23 . Joint instability is a determinant of pain in OA 24,25 . Therefore, we can emphasize that a degradation of fibulin-3 is associated with ligament hyperlaxity, joint instability, and subsequently with pain.…”
Section: Discussionmentioning
confidence: 99%
“…It's a major risk factor in the development of OA 23 . Joint instability is a determinant of pain in OA 24,25 . Therefore, we can emphasize that a degradation of fibulin-3 is associated with ligament hyperlaxity, joint instability, and subsequently with pain.…”
Section: Discussionmentioning
confidence: 99%
“…Aunan et al have shown poor outcome scores (Knee Injury & Osteoarthritis Outcomes Score (KOOS), Oxford Knee Score and Knee Society Score (KSS)) in patients who had >2 mm laxity in extension and >3 mm laxity in flexion 19. Gustke et al also showed statistically inferior KSS (145.3 vs 172.4) and Western Ontario  and McMaster Universities Arthritis Index (WOMAC) scores (23.6 vs 14.5) for unbalanced knees compared with the group of balanced knees 7…”
Section: Discussionmentioning
confidence: 99%
“…The surgeon decides how stiff or loose total knee he would like to achieve. There are no objective methods to evalu ate ideal collateral tension intraoperatively, the sur geon's experience still being the best guide [3,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Głów nym ce lem całko wi tej en do pro te zo pla sty ki sta wu ko la no we go nadal są: znie sie nie bó lu oraz przy wró ce nie funk cji stawu. Od two rze nie ana to micz nej osi ko la na, wła ściwe go ba lan su wię za dło we go i do bre go za kre su ruchu w istot ny spo sób wpły wa ją na po ope ra cyj ny wynik pa cjen ta [3]. W przy pad ku ko lan z przed ope racyj ną de for ma cją ko śla wą bądź szpo ta wą za bieg, endo pro te zo pla sty ki jest bar dziej wy ma ga ją cy ze wzglę du na ko niecz ność nie jed no krot nie roz le głe go uwal nia nia tka nek mięk kich [4], a ta kże uzu peł nie nia ewen tu al nych ubyt ków kost nych [5,6].…”
Section: Wstępunclassified
See 1 more Smart Citation